Athlete365 Survey findings (IOC, 2020)
The aim of this survey conducted by the International Olympic Committee (IOC) in May 2020 was to understand the challenges faced in this current climate (COVID-19) from different audience groups.The survey was translated into 8 languages and respondents came from 135 countries. The survey revealed that managing mental health and sports careers, as well as nutrition and diet, were the biggest challenges faced by athletes during the unprecedented time of the COVID-19 pandemic.